Retrospective analysis on the efficacy of the use of tocilizumab in patients with severe pneumonia due to SARS-CoV-2 (Actualizaciones en Sida e Infectología, 2024)
SARS-CoV-2 infection can lead to adult acute respiratory distress syndrome. The only treatment that has been shown to reduce mortality is dexamethasone. Tocilizumab shows promise in inhibiting IL-6. The absence of local evidence on its efficacy motivated this retrospective, analytical and observational study, from 6/1/21 to 2/28/23, which aims to analyze mortality, oxygen requirement, days of hospitalization and complications of hospitalized patients with COVID19. patients who received tocilizumab compared to a control group who received standard care. Twenty-seven patients who received tocilizumab and 69 in the control group were included. The average number of sick days when receiving tocilizumab was 11.96. We found a non-statistically significant trend of lower mortality (29 vs 14.8% p=0.19), days of ICU hospitalization (13 vs 19 p=0.6), high-flow oxygen requirement (22 vs 45 p =0.11), respiratory mechanical assistance (5 vs 21 p=0.23), infectious complications (18.5 vs 27.5% p=0.35) and non-infectious (11 vs 21.7% p=0 ,23), in the group that received tocilizumab with a tendency to increase PAFI and decrease C-reactive protein 48 hours after its infusion. The use of tocilizumab could be associated with lower mortality, days spent in the ICU, need for MRA, and complications during hospitalization, in seriously ill patients, which seems to be related to an improvement in the hyperinflammatory state. Since it is a single-center study with a low number of patients, it should be expanded to obtain more evidence of this effect.La infección por SARS-CoV-2 puede generar un síndrome de dificultad respiratoria aguda del adulto. El único tratamiento que demostró disminuir la mortalidad es la dexametasona. El tocilizumab es prometedor al inhibir la IL-6. La ausencia de evidencia local sobre su eficacia motivó este estudio restrospectivo, analítico y observacional, desde 1/6/21 al 28/2/23 que tiene como objetivos analizar mortalidad, requerimiento de oxígeno, días de internación y complicaciones de pacientes internados con COVID19 grave que recibieron tocilizumab respecto a un grupo control que recibió cuidados estándar. Se incluyeron 27 pacientes que recibieron tocilizumab, y 69 en el grupo control. El promedio de días de enfermedad al recibir tocilizumab fue de 11,96. Encontramos una tendencia no estadísticamente significativa de menor mortalidad (29 vs 14,8% p=0,19), días de internación en UTI (13 vs 19 p=0,6), requerimiento de oxígeno a alto flujo (22 vs 45 p=0,11), asistencia mecánica respiratoria (5 vs 21 p=0,23), complicaciones infecciosas (18,5 vs 27,5% p=0,35) y no infecciosas (11 vs 21,7% p=0,23), en el grupo que recibió tocilizumab con tendencia al aumento de PAFI y disminución de proteína C reactiva a las 48 horas de su infusión. El uso de tocilizumab podría asociarse a menor mortalidad, días de internación en UTI, necesidad de ARM y de complicaciones durante la internación, en pacientes grave, lo que impresiona estar en relación con una mejoría del estado hiperinflamatorio. Debido a que es un estudio unicéntrico y con bajo número de pacientes, debería ampliarse para obtener mayor evidencia de dicho efecto.
Keywords: Tocilizumab; Severe pneumonia; SARS-CoV-2